Survival Analysis of Trabeculectomy and Phacotrabeculectomy in Primary Angle Closure Glaucoma - Gustianty, Elsa; Shalim, Nikho Melga; Virgana, Rova; Prahasta, Andika; Rifada, R. Maula; Umbara, Sonie (Majalah Kedokteran Bandung, 2024)
Glaucoma is the global leading cause of irreversible blindness. Primary angle closure glaucoma occurs most frequently in Asian populations, including in Indonesian population. Surgical management of Primary Angle Closure Glaucoma (PACG) includes cataract extraction, trabeculectomy, or combined phacotrabeculectomy. Many patients presented in the advanced stages of the disease with significant cataracts, requiring combined surgery. This study aimed to determine whether trabeculectomy alone was better in reducing intraocular pressure compared to phacotrabeculectomy in primary angle closure glaucoma. This was an analytic retrospective observational study reviewing medical records of PACG patients underwent trabeculectomy or phacotrabeculectomy from January to December 2015, within a 5-year follow-up period of a tertiary eye hospital. The success rates of the two groups were assessed with Kaplan-Meier survival analysis. Success criteria were defined as > 20% reduction of IOP or IOP <21 mmHg with or without medication. Results showed 104 and 41 eyes underwent trabeculectomy and phacotrabeculectomy, respectively. The cumulative 5-year survival rate in trabeculectomy group was 58.6%, and 85.4% in phaco trabeculectomy. There was no statistical difference in the success rate between the trabeculectomy and phaco trabeculectomy groups (p=0.102). Postoperative complications observed in the phacotrabeculectomy group were one choroidal detachment, one malignant glaucoma, and one vitreous prolapse. Thus, the cumulative success rate of phacotrabeculectomy was better than trabeculectomy after 5 years of follow up, albeit not statistically significant.